“Constructive Paranoia” Applied to Education (The Case of English Language Teaching) - Barrantes Montero, Luis Guillermo (Revista Electrónica Educare, 2012)
This paper analyzes the concept of constructive paranoia stated by journalist and author Andrés Oppenheimer to promote development in Latin America. Based on that concept, this paper discusses the effectiveness of current English Language Teaching, particularly, as well as what should be done in order to obtain better results. As a conclusion, a re-structure of approach, curriculum and methodology in teaching the language is proposed.